Apolipoprotein C3 and circulating mediators of preadipocyte proliferation in states of lipodystrophy - Brandao Bruna Brasil; Sakaguchi Masaji; Batista, Thiago Martins; Hu Jiang; Nie Song; Schepmoes Athena A; BonDurant Lucas; Moreau François; Qian Wei-Jun; Kulkarni N. Rohit; Kahn, C. Ronald (Elsevier, 2022)
Adipogenesis is a complex process controlled by intrinsic and extrinsic factors that regulate preadipocyte proliferation, adipogenic capacity and maturation of metabolic function. Here we show that insulin and IGF-1 receptors are essential for mature adipocyte survival and that deletion of both IR and IGF1R specifically in fat using a tamoxifen inducible-AdipoQ-Cre (Ai-DKO) leads to rapid and severe loss of adipocytes in all depots, associated with a metabolic syndrome characterized by hypertriglyceridemia, hyperglycemia, hyperinsulinemia, fatty liver, and pancreatic beta cell proliferation. In this model, this pathological phenotype reverses over a few weeks, in large part, due to preadipocyte proliferation and adipose tissue regeneration. Incubation of preadipocytes with serum from the Ai-DKO mice in vitro stimulates cell proliferation, and this effect can be mimicked by conditioned media from liver slices of Ai-DKO mice, but not by media of cultured Ai-DKO adipocytes, indicating a hepatic origin of the growth factor. Proteomic analysis of serum reveals apolipoprotein C3 (APOC3), a protein secreted by liver, as one of the most upregulated proteins in the Ai-DKO mice. In vitro, purified and delipidated APOC3 stimulates preadipocyte proliferation, however, knockdown of hepatic APOC3 in vivo in Ai-DKO mice is not sufficient to block adipose regeneration. Thus, lipodystrophy is associated with presence of increased preadipocyte-stimulating growth factors in serum. Our study indicates that APOC3 is one contributing factor to preadipocyte proliferation, however, other still-unidentified circulating growth factors are also likely present in Ai-DKO mice. Identification of these factors may provide a new approach to regulation of adipose mass in health and disease.